A review on fatigue damages in the wind turbines: Challenges in determining and reducing fatigue failures in wind turbine blades. Issue 4 (August 2020) - Ravikumar, Karthikeyan; Subbiah, Rajkumar; Ranganathan, Nalini; Bensingh, Joseph; Kader, Abdul; Nayak, Sanjay K
The wind energy has been recognised as one of the rising sustainable energies in the world. The wind turbines are subjected to high aerodynamic loads and they cause vibrations due to the wake formation. The magnitude of the applied loads has significant effects on the crack propagation. The fatigue loads have been identified as one of the key sources of damage, with delamination as the main cause for the failure of the turbine blades. The article presents a review of fatigue damages that have been experienced in the wind turbine blades, and factors that are influenced due to the fatigue loads are discussed. The causes and effects of the fatigue loads have been highlighted, and the ways for preventing the fatigue damage by improving the design lifetime are mainly concentrated in review. The overall review gives an idea for determining and reducing the crack growth in wind turbine blades.